Using CDS Hooks to increase SMART on FHIR app utilization: a cluster-randomized trial. (31st May 2022) - Morgan, Keaton L; Kukhareva, Polina V; Warner, Phillip B; Wilkof, Jonah; Snyder, Meir; Horton, Devin; Madsen, Troy; Habboushe, Joseph; Kawamoto, Kensaku
Abstract: Objective: HL7 SMART on FHIR apps have the potential to improve healthcare delivery and EHR usability, but providers must be aware of the apps and use them for these potential benefits to be realized. The HL7 CDS Hooks standard was developed in part for this purpose. The objective of this study was to determine if contextually relevant CDS Hooks prompts can increase utilization of a SMART on FHIR medical reference app (MDCalc for EHR). Materials and Methods: We conducted a 7-month, provider-randomized trial with 70 providers in a single emergency department. The intervention was a collection of CDS Hooks prompts suggesting the use of 6 medical calculators in a SMART on FHIR medical reference app. The primary outcome was the percentage of provider–patient interactions in which the app was used to view a recommended calculator. Secondary outcomes were app usage stratified by individual calculators. Results: Intervention group providers viewed a study calculator in the app in 6.0% of interactions compared to 2.6% in the control group (odds ratio = 2.45, 95% CI, 1.2–5.2, P value .02), an increase of 130%. App use was significantly greater for 2 of 6 calculators. Discussion and Conclusion: Contextually relevant CDS Hooks prompts led to a significant increase in SMART on FHIR app utilization. This demonstrates the potential of using CDS Hooks to guide appropriate use of SMART on FHIR apps and was a primary motivation for the development of the standard. Future research may evaluate potential impacts on clinical care decisions and outcomes.